Differences in Governance Practices between U. S. and Foreign Firms: Measurement, Causes, and Consequences - Aggarwal, Reena; Erel, Isil; Stulz, René; Williamson, Rohan (Review of Financial Studies, 2009)
[We construct a firm-level governance index that increases with minority shareholder protection. Compared with U.S. matching firms, only 12.68% of foreign firms have a higher index. The value of foreign firms falls as their index decreases relative to the index of matching U.S. firms. Our results suggest that lower country-level investor protection and other country characteristics make it suboptimal for foreign firms to invest as much in governance as U.S. firms do. Overall, we find that minority shareholders benefit from governance improvements and do so partly at the expense of controlling shareholders.]